EP 97. Strength lies in peace. Cognitive stress reduces the effect of levodopa on Parkinson's resting tremor. Issue 9 (September 2016) - Zach, H.; Dirkx, M.; Pasman, J.; Bloem, B.R.; Helmich, R.C.
Abstract : Background: Resting tremor in Parkinson's disease (PD) is markedly increased during cognitive stress. Dopamine depletion in the basal ganglia has a role in the pathophysiology of resting tremor, but it is unclear whether this contribution varies between behavioral settings. Here, we test the hypothesis that levodopa effect on resting tremor amplitude and variability alters during rest and cognitive co-activation. Methods: We included 69 PD patients with prominent resting tremor. Patients were measured both OFF medication and after levodopa-benserazide 200/50 mg, using clinical scores (MDS-UPDRS) and accelerometry. We compared two contexts: rest and cognitive co-activation (counting backwards in steps of 7 as fast as possible). We investigated the influence of levodopa and cognitive co-activation, and the interaction between these factors, on resting tremor amplitude and variability. Results: Levodopa significantly reduced maximal resting tremor intensity, while cognitive co-activation increased it ( p < 0.001 ). Crucially, the levodopa effect was significantly smaller during cognitive co-activation than during rest. In other words, the positive effect of levodopa was counteracted by a negative effect of cognitive stress (sign. TREATMENT × CONTEXT interaction, p  = 0.02). Furthermore, levodopa significantly increased resting tremor variability but variability was smaller during cognitive co-activation ( p < 0.001 ; here without sign. TREATMENT × CONTEXT interaction). Conclusion: Cognitive co-activation reduced the levodopa effect on resting tremor and it reduced tremor variability. This underlines the importance of simple counting tasks in clinical practice, as measurements at rest will overestimate the treatment effect. The reduced levodopa effect during cognitive stress might be caused by non-dopaminergic mechanisms amplifying tremor. Future research aims to identify clinical, electrophysiological and cerebral factors influencing the levodopa effect on resting tremor.